Menakar Kembali Nilai Keperempuanan: Analisis Pascastrukturalisme atas Tiga Karya - Prasetyo, Teguh (Sekolah Pascasarjana Institut Kesenian Jakarta, 2023)
In the construction of patriarchal culture, women and the values that accompany them are often placed in a position that is destined to be supporting and below the position of men. Literary works were born as a response to the cultural conditions that accompanied them. On the one hand, it can be a mirror, but on the other hand, it can also be a stimulus for critical thinking about the culture itself. Literary works such as Pengakuan Pariyem by Linus Suryadi A.G.,